Analytical dispersion model for the chain of primary and secondary air pollutants released from point source. (March 2016) - Juodis, Laurynas; Filistovič, Vitold; Maceika, Evaldas; Remeikis, Vidmantas
Abstract: An analytical model for dispersion of air pollutants released from a point source forming a secondary pollutant (e.g. chemical transformation or parent-daughter radionuclide chain) is formulated considering the constant wind speed and eddy diffusivities as an explicit function of downwind distance from the source in Cauchy (reflection-deposition type) boundary conditions. The dispersion of pollutants has been investigated by using the Gaussian plume dispersion parameters σ y and σ z instead of the diffusivity parameters K y and K z . For primary pollutant it was proposed to use the derived dry deposition factor instead of the source depletion alternative. An analytical solution for steady-state two-dimensional pollutant transport in the atmosphere is presented. Derived formulas include dependency from effective release height, gravitational and dry deposition velocities of primary and secondary pollutants, advection, surface roughness length and empirical dispersion parameters σ y and σ z . Demonstration of analytical solution application is provided by calculation of 135 Xe and 135 C air activity concentrations and the applicability of the model for the solution of atmospheric pollution transport problems. Highlights: We propose the model for primary and secondary pollutant dispersion in the atmosphere. Analytical model takes into account processes of pollutant transformation and removal. Used diffusivity coefficients K i are expressed through the dispersion parameters σ i . We provide analytical expressions of solution for pollutant chain dispersion.